Determinismo/indeterminismo y determinación: implicaciones en el campo de la salud pública (2013)
ABSTRACT: The purpose of this paper is to analyze the categories of determinism and indeterminism in the Public Health field and to establish the differences between these categories and that of the social determination proposed in the context of Latin American Public Health. It is suggested that both determinism and indeterminism are insufficient terms to explain the complexity of health and life, not only in the epistemic map but also in the framework of ethical analysis. Instead, the notion of determination is presented as a complex category that makes it possible to approach the problems related to health and life from their dialectic relationships with social, politic, cultural and economic conditions. Finally, some of the main differences between the Social determinants of health approach proposed by the who and the Social determination of health and life approach proposed by the Latin American Public Health are presented.